Mirror Neuron Cells, Autism, Language Deficit, and the Potential Role of Artificial Intelligence - Alkhatib, Ahed J; Darabseh, Rahaf Salem (Journal of Ecohumanism, 2024)
Mirror neuron cells were first found in the macaque monkey cortex and subsequently reported in the inferior frontal and parietal lobes. Due to the activation of this neural apparatus during goal understanding, some scholars believe that mirror neurons are involved in one of the cognitive aspects of understanding, called action understanding. Later, it was argued that this system was involved in various social-cognition aspects, such as theory of mind, learning by observation, and empathy, which allow human beings to predict the behavior of others, transmit social knowledge, and grasp the states of mind of others. Some descriptions even give mirror neuron cells the ability to communicate without any conscious effort, with words, or beyond words. Researchers used proposals about mirror neuron cells to investigate the language of origin, social cognition, and human evolution. Like many new ideas, mirror neuron cells have caused a major reflection and a significant increase in academic activity. There are now about 4,000 papers on the topic. The production of behaviors is possible because of a complex interplay between perception and action. Component analysis of complex behavior is explained by the presence of neural circuits and complex cell activation patterns that model the predicted outcome derived from either performed or observed actions and consequently generate the actual physical performance. It is suggested, therefore, that knowledge of behavior, both own and others’, could be organized in terms of acquired neural activity. The mirror neurons, reacting during observation and execution of the same motor act, would provide such neural means, blurring the experimental distinction between self-action and other action. Behavioral research on humans has shown enhanced memory and kinematic facilitation processes for action features that are either compatible or congruent with observed movement. However, only a few studies have so far been able to link these parametric effects to distinct changes in the cortical pattern of activity in the observer. Despite the widespread acceptance in the recent experimental literature, there is no definitive evidence for the existence of an MNS. Furthermore, contrasting evidence comes from transcranial brain stimulation investigations and from a few studies on patients with focal brain lesions. The broken MNS hypothesis and its models may offer more parsimonious and cognitively coherent accounts of ASC. Finally, it seems clear that imitation refers not only to mirroring processes but also to emulation/mimicry mechanisms underlying the formation of pragmatic and communicative aspects of imitation critically impaired and impoverished in ASC.